Diagnosis and management of small bowel obstruction in the ileum caused by endometriosis: A case report - Nora Gillen; Timea Kovacs; Jada Leahy (Elsevier, 2023)
Small bowel obstruction is a rare complication of endometriosis, a condition defined by the presence of endometrial tissue outside of the uterine cavity. The rectosigmoid junction is the most common site for intestinal endometriosis. However, small bowel involvement, particularly of the ileum, is less common, and is a much rarer location for endometriosis causing bowel obstruction.A 37-year-old woman with a medical history of endometriosis requiring multiple abdominal surgeries presented with signs and symptoms of small bowel obstruction. Computerized tomography indicated a transition point at the terminal ileum. Conservative treatment did not alleviate her symptoms, and so a right hemicolectomy was performed to relieve her obstruction. Endometriosis of the ileum was discovered on intraoperative pathology.The diagnosis of endometriosis and treatment options, especially as they relate to imaging techniques, are currently limited. There is a need for an improvement in the diagnosis of endometriosis. Advanced imaging techniques may lead to a more patient-centered approach to treatment in cases of small bowel obstruction. Prior to obstruction, serial imaging might catch the proliferation of endometrial tissue into the bowel. Conservative treatment might be tailored to endometriosis to help relieve obstruction and in surgical management resection margins might be adjusted to help preserve the bowel. This would improve patient quality of life by improving treatment.